2018
DOI: 10.1029/2018gc007691
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Deformation in the Eastern Himalaya, Burmese Arc and Adjoining Regions

Abstract: This study presents new results of shear wave splitting at 56 broadband stations installed in the Eastern Himalaya, Burmese Arc, and adjoining regions. The fast polarization directions (FPDs) within the Himalaya, Burmese Arc and the foredeep are parallel to the strike of the orogens, suggesting a coherently deformed lithospheric mantle under compression. The FPDs follow the Main Boundary Thrust and the Main Central Thrust in the central segment of the Arunachal Himalaya. Smaller delay times (∼0.7 s) can be bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…A recent study in the Eastern Himalaya also found that the FPAs are mostly oriented along the arc curvature, lending credence to the hypothesis that lithospheric deformation is the primary source of anisotropy [26]. Further west in the Sikkim Himalaya, strike parallel FPA orientation follows [19].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…A recent study in the Eastern Himalaya also found that the FPAs are mostly oriented along the arc curvature, lending credence to the hypothesis that lithospheric deformation is the primary source of anisotropy [26]. Further west in the Sikkim Himalaya, strike parallel FPA orientation follows [19].…”
Section: Discussionmentioning
confidence: 68%
“…Further, due to the higher convergence rate, the amount of shortening is found to be more for the eastern Himalaya [49]. This might cause the FPAs in Arunachal Himalaya to orient along the strike of the orogen, suggesting that the coherently deformed mantle is under compression [26]. The amount of shortening decreases towards west.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…On the Indian plate, while some early studies (Barruol & Hoffmann, ; Chen & Özalaybey, ; Sandvol et al, ) suggest a lack of observable splitting based on measurements at a few stations, significant anisotropy is detected by most of the more recent investigations (Figure ; Hazarika et al, ; Heintz et al, ; Saikia et al, , ; Singh et al, , ). Using data from 56 broadband seismic stations in the eastern Himalayan and Burmese arc region, Saikia et al () report weak orogen‐parallel anisotropy. Weak or the absence of anisotropy reported at stations on the Indian plate is attributed to multiple layers of anisotropy with nearly orthogonal fast orientations.…”
Section: Previous Sws Studies In the Vicinity Of The Ehsmentioning
confidence: 93%